Uncovering the Uncommon Nocardia Keratitis: Early Recognition of Its Pathognomonic Characteristic to Save Vision: Poster Presentation - Case Report - Resident - Maria Astrid Claudia; Ismi Zuhria (Majalah Oftalmologi Indonesia, 2023)
Introduction : Nocardia keratitis is a rare bacterial infection. Global prevalence is below 2%. Mimicking a fungal infection and slow-growth bacteria in culture leads to improper management and an increased risk of permanent vision loss. This case highlights the pathognomonic infiltrate seen in Nocardia keratitis. Case Illustration : A 41-year-old male presented with a four-week history of redness of the left eye, associated with ocular pain, tearing, photophobic, and decreased vision following an injury caused by a grasshopper while riding a motorcycle two weeks before. Visual acuity was hand movement. Conjunctival and ciliary injection, mid-periphery corneal “wreath-pattern” infiltrate with satellite lesions, corneal thinning, and hypopyon were found. Topical antibiotics and antifungals were given empirically earlier with little to no effect. Progressive hypopyon necessitated paracentesis. After seven days of inoculation, a culture test showed slow-growing Nocardia sensitive to amikacin and tobramycin. Treatment then changed to an amikacin subconjunctival injection and tobramycin eye drops. The epithelial defect was resolved, but leukoma and neovascularization were found; thus, keratoplasty was planned. Discussion : Corneal involvement of Nocardia may occur in several forms. Slowly progressive symptoms, satellite lesions, and cotton-wool-like infiltrate can mimic fungal infection. However, it has a pathognomonic characteristic, a pinhead-sized infiltrate forming a “wreath-pattern” in the mid-periphery cornea. Familiarity with this classical pattern could prevent neovascularization, endophthalmitis, corneal perforation, and that cause vision loss. Conclusion : Due to slow-growth inoculation of Nocardia, clinicians should be aware of this pathognomonic presentation to aid in early diagnosis and proper treatment that leads to favorable outcomes and salvage vision in most cases.